The influence of evidence-based nutritional support plans on the nutritional status and adverse effects of radiotherapy in individuals with nasopharyngeal carcinoma - Fan, Xiaomei; Cui, Huixia; Peng, Haibo; Liu, Shasha; Jiang, Li (Frontiers in Nutrition, 2025)
ObjectiveRadiotherapy serves as the primary treatment for patients with nasopharyngeal carcinoma (NPC). However, it frequently results in a progressive decline in nutritional status, which is linked to unfavorable clinical outcomes. This study aims to evaluate the effects of an evidence-based nutritional support program on nutritional status, radiotherapy-related side effects, and quality of life (QoL) in NPC patients undergoing radiotherapy.MethodsA historical control trial was conducted. Patients with NPC admitted between May 2023 and August 2023 were allocated to the control group and received routine care, whereas those admitted between September 2023 and December 2023 were assigned to the intervention group and provided with a multidisciplinary, professional, individualized, and comprehensive evidence-based nutritional support program. Nutritional status was assessed through anthropometric measurements (e.g., body mass index, BMI), laboratory indicators (hemoglobin and albumin levels), the Nutritional Risk Screening 2002 (NRS2002), and the Patient-Generated Subjective Global Assessment (PG-SGA). Additionally, radiotherapy-related side effects, radiotherapy interruption rates, and QoL were monitored.ResultsBoth groups comprised 40 patients each. By the conclusion of radiotherapy, a decline in nutritional status was observed in both groups; however, BMI was higher in the intervention group (23.14 ± 2.62) compared to the control group (21.38 ± 2.73). The NRS2002 score (2.73 ± 1.45) and PG-SGA score (6.13 ± 3.22) in the intervention group were significantly lower than in the control group (3.33 ± 1.16 and 7.73 ± 2.72, respectively; p < 0.05). The incidence of severe malnutrition was significantly lower in the intervention group (52.5%) compared to the control group (75%) (p < 0.05). Albumin and hemoglobin levels were significantly higher in the intervention group (albumin: 120.75 ± 16.52 vs. 113.50 ± 12.08, p = 0.028; hemoglobin: 41.24 ± 4.54 vs. 37.62 ± 5.04, p = 0.001). The severity of radiotherapy-related side effects, including radiation-induced oral mucositis, dermatitis, and myelosuppression, was significantly lower in the intervention group (p < 0.05). All patients completed radiotherapy, and no significant difference was observed in radiotherapy interruption rates between groups (control group: 6 interruptions; intervention group: 1 interruption; p > 0.05). Post-radiotherapy QoL scores demonstrated that the intervention group achieved superior outcomes in physical, role, emotional, cognitive, and social functioning (p < 0.05).ConclusionImplementing evidence-based nutritional support programs has the potential to prevent the decline in nutritional status among NPC patients receiving radiotherapy, reduce the occurrence of treatment-related side effects, and enhance overall quality of life.